Pengaruh Pengembangan Kompetensi Sumber Daya Manusia Terhadap Kinerja Pegawai - Rusdi Rusdi (Universitas 17 Agustus 1945 Samarinda, 2020)
This study aims to determine whether the pattern of human resources competency development and performance of employees and the impact of competence development of human resources to employee performance Siluq Ngurai District of Kutai Barat. The results showed that the variable competence of human resources does not have a positive relationship with employee performance variables. It can be seen from the comparison between the value of r empirical (count) with the value of r theoretical (table) in the table prices are critical to r product moment, i.e. r (hit) = 0.052 < r (tab) = 0.288 at a significance level 0 05 to n = 45. This means that there is no positive relationship and influence between variable competence development of human resources with performance variables. The results show that the resulting R-Square is 0,003, which means contributions competence development of human resources to employee performance is only 0.03%. This means that there is no significant influence of the competence of human resources development variables to variable employee performance Penelitian ini bertujuan untuk mengetahui apakah pola pengembangan kompetensi sumber daya manusia dan kinerja pegawai serta dampak pengembangan kompetensi sumber daya manusia terhadap kinerja pegawai Kecamatan Siluq Ngurai Kabupaten Kutai Barat. Hasil penelitian menunjukkan bahwa kompetensi variabel sumber daya manusia tidak memiliki hubungan positif dengan variabel kinerja karyawan. Hal ini dapat dilihat dari perbandingan antara nilai r empiris (hitungan) dengan nilai r teoritis (tabel) dalam harga tabel sangat penting untuk r momen produk, yaitu r (hit) = 0,052 < r (tab) = 0,288 pada tingkat signifikansi 0 05 sampai n = 45. Ini berarti bahwa tidak ada hubungan positif dan pengaruh antara pengembangan kompetensi variabel sumber daya manusia dengan variabel kinerja. Hasil penelitian menunjukkan bahwa R-Square yang dihasilkan adalah 0.003, yang berarti kontribusi pengembangan kompetensi sumber daya manusia untuk kinerja karyawan hanya 0,03%. Ini berarti bahwa tidak ada pengaruh signifikan dari kompetensi variabel pengembangan sumber daya manusia terhadap kinerja karyawan yang bervariasi.